1884 Supplement to the Revised Statutes of the State of Ohio, at 633, Licenses, § 24 - (:unkn) unknown (My University, 1884)
All vendors of gunpowder shall pay a license fee of fifteen (15) dollars per annum. All keepers or owners of gunpowder magazines shall pay a license fee of one hundred (100) dollars per annum.
Keywords: LICENSE - DEALERS